Ð”Ð¸Ñ„Ñ„ÑƒÐ·Ð¸Ñ Ð¼Ð½Ð¾Ð³Ð¾Ð°Ñ‚Ð¾Ð¼Ð½Ñ‹Ñ… ÑÐ¿Ð¸Ñ€Ñ‚Ð¾Ð² Ð¸ Ð¸Ñ… Ð¼ÐµÑ‚Ð¾ÐºÑÐ¸Ð¿Ñ€Ð¾Ð¸Ð·Ð²Ð¾Ð´Ð½Ñ‹Ñ… Ñ‡ÐµÑ€ÐµÐ· Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½Ñ‹ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² ÐºÑ€Ñ‹ÑÑ‹ Ð¸ ÐºÑ€Ð¾Ð»Ð¸ÐºÐ° - Kovalenko, G. V.; Kovalenko, I. F.; Linnik, T. P.; Koshchiy, S. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
There were determined the coefficients for membrane permeability of rat and rabbit native erythrocytes for glycerol, ethylene glycol molecules, their methoxyderivatives at 25 and 37°C, as well as erythrocytes, incubated with mercury sulfhydryl reagent (pCMBS): the band 3 protein blocker at 25°C. The activation energy of the process of cryoprotectant molecule transfer through erythrocyte membranes at 25 and 37°C and after incubation with pCMBS was calculated. The rate of substance diffusion into rat erythrocytes was shown to be higher, than in rabbit ones. As an example the coefficient of EG permeability into rat and rabbit erythrocytes at 37°C is equal to 13.95x10-6 and 5.21x10-6 m/sec, correspondingly. The rate of transmembrane diffusion of EG and glycerol methoxyderivatives is 50–80 times higher, compared to EG and glycerol. There was proposed and discussed in details the transport mechanism of studied substances through rat and rabbit erythrocyte membranes.